Features of bacterial and fungal communities in the rhizosphere of Gastrodia elata cultivated in greenhouse for early harvest - Khanh, Nguyen Van; Dutta, Swarnalee; Kim, Chang-Su; Lee, Yong Hoon (Frontiers in Microbiology, 2024)
Symbiotic microbes are essential for developing and growing Gastrodia elata, an achlorophyllous orchid of high medicinal value. Recently, the cultivation of G. elata in greenhouses has been adopted in Korea to produce mature tubers in a short time. However, no studies have been conducted on the microbial community structure of G. elata cultivated in greenhouse environments. Therefore, we analyzed the temporal features of bacterial and fungal communities in the rhizosphere of G. elata at the juvenile (JT; 2 months after sowing (MAS)), young (YT; 6 MAS), and mature (MT; 11 MAS) tuber stages using culture-dependent and high-throughput sequencing technology. The richness and diversity of the bacterial and fungal communities decreased with tuber growth of G. elata. The symbiotic fungi Mycena sp. and Armillaria sp. as well as tuber extract inhibited the growth of various soil-inhabiting fungal and bacterial strains, indicating that G. elata and its symbiotic fungi play important roles in the selection of rhizosphere microbes. Mortierella rishikesha was the most abundant fungal species in the rhizosphere. We also identified the microorganisms potentially beneficial for G. elata development during greenhouse cultivation. Tubers and symbiotic fungi actively exert selective pressure on rhizosphere microbes, influencing the diversity and abundance of bacterial and fungal communities as G. elata grows. This study is a first report on the temporal microbial community structure of G. elata cultivated in greenhouse. The results on the associated microbiome of G. elata will help understand their beneficial interactions with G. elata and contribute to improvement in cultivation.